PSYCHOLOGICAL PRINCIPLES OF TECHING ENGLISH - Abdurahmonova, Zebo (Журнал иностранных языков и лингвистики, 2023)
Language is a complex whole, the mastery of which requires the learner’s total commitment for life. The person’s prior knowledge, attitudes, personality, learning styles, skills and motivation are all factors related to eventual outcome of the language study (Brown, 2004). Language, so far as we know, is something specific to humans, that is to say it is the basic capacity that distinguishes humans from all other living beings. Language therefore remains potentially a communicative medium capable of expressing ideas and concepts as well as moods, feelings and attitudes.